2011
DOI: 10.1108/09526861111150699
|View full text |Cite
|
Sign up to set email alerts
|

Individual personal relations: effects on service quality

Abstract: Better quality of care involves changing patient perceptions and attitudes to what constitutes nursing competence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Theory-generating studies (n= 2) demonstrated the importance of nursing interventions in the oncology population that promoted trust in the patient–nurse relationship (Charalambous et al, 2016; Radwin et al,2009). Six studies focused on a specific cancer diagnosis: breast (n=3), colorectal (n=1), lung (n=1), and prostate (n=1) (Bando et al, 2018; Holopainen et al, 2014; Jakobsson & Holmberg, 2011; Koinberg et al,2002; Montpetit & Singh-Carlson, 2018; Tuominen et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Theory-generating studies (n= 2) demonstrated the importance of nursing interventions in the oncology population that promoted trust in the patient–nurse relationship (Charalambous et al, 2016; Radwin et al,2009). Six studies focused on a specific cancer diagnosis: breast (n=3), colorectal (n=1), lung (n=1), and prostate (n=1) (Bando et al, 2018; Holopainen et al, 2014; Jakobsson & Holmberg, 2011; Koinberg et al,2002; Montpetit & Singh-Carlson, 2018; Tuominen et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Another critical attribute in nurses that facilitates patient–nurse trust is a positive nurse attitude. In a study that included patients diagnosed with prostate cancer (n=11), the attitude of the nurse as being “nice and cheerful” influenced the perception of the nurse as being confident and, therefore, trustworthy (Jakobsson & Holmberg, 2011, p. 434). Nurses who readily smile and appear gracious are also perceived as having positive attributes as reported by patients in a study by Ozaras and Abaan (2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations